Synthesis, characterization and comparative study the antibacterial activities of some imine-amoxicillin derivatives - Tomi, Ivan Hameed Rouil; Abdullah, Amer Hasan; Al-Daraji, Ali Hussein Raheemah; Abbass, Selma Abdul Rudha (European Journal of Chemistry, 2013)
In this study, we report the synthesis of some new Schiff base compounds (1-5) from the reaction of amoxicillin with some aromatic aldehydes in classical Schiff base method. These derivatives were characterized by melting point, elemental analysis, FT-IR and 1H NMR data. All the synthesized compounds were evaluated in vitro for their antibacterial activities against two Gram positive (Staphylococcus aureus, Streptococcus faecalis) and two Gram negative (Escherichia coli, Pseudomonas aeruginosa) microorganisms in different concentrations (10-1, 10-3, 10-5 and 10-7 M) by agar diffusion disk method. The results showed that some of these derivatives have good antibacterial activities compared to biological activity of parent drug.